Pro‐ and anti‐inflammatory cytokines mediate the progression of severe anemia in malaria‐infected children: A prospective study - Charles Nkansah; Felix Osei‐Boakye; Gabriel Abbam; Samuel K. Appiah; Samira Daud; Bright Boakye; Samsiyatu Abdulai; Madina Ahmed; Theophilus B. Antwi; Birago Boateng; Miigbat P. Libatin; Alexander S. Mensah; et al. (Immunity, Inflammation and Disease)
Abstract Background Severe Plasmodium falciparum malarial anemia is still the principal cause of death in children in underdeveloped countries. An imbalance between proinflammatory and anti‐inflammatory cytokines is associated with malaria progression. This study evaluated circulating levels of selected inflammatory cytokines among malaria‐infected children in Ghana. Methods This case‐control study was conducted at Tamale Teaching Hospital, Ghana. One hundred and twenty children with malaria and 60 controls, aged 12−144 months were selected from April to July, 2023 for the study. Malaria was diagnosed through microscopy, full blood count was measured using hematology analyzer, and cytokines were measured using enzyme‐linked immunosorbent assay. Results Malaria‐infected children had higher tumor necrosis factor alpha (TNF‐α) (p < .001), interferon‐gamma (IFN‐ɣ) (p < .001), interleukin (IL)‐1β (p < .001), IL‐6 (p < .001), granulocyte macrophage‐colony stimulating factor (GM‐CSF) (p < .001), and IL‐10 (p < .001) levels than controls. Participants with high parasitemia had raised TNF‐α (p < .001), IFN‐ɣ (p < .001), IL‐1β (p < .001), IL‐6 (p < .001), GM‐CSF (p < .001), and IL‐10 (p < .001), but reduced IL‐3 (p < .001) and TGF‐β (p < .001) than those with low parasitemia. Severe malarial anemic children had elevated TNF‐α (p < .001), IFN‐ɣ (p < .001), IL‐1β (p < .001), IL‐6 (p < .001), GM‐CSF (p < .001), and IL‐10 (p < .001), but lower IL‐3 (p < .001) and TGF‐β (p < .001) than those with uncomplicated malaria. Conclusion Parasite density was the principal predictor of the cytokine levels, as parasitemia positively associated with IL‐10, GM‐CSF, IL‐6, IL‐1β, IFN‐ɣ, and TNF‐α, but negatively associated with IL‐3 and TGF‐β. Malaria is associated with enhanced secretion of pro‐ and anti‐inflammatory cytokines in Ghanaian children. Inflammatory cytokines may be involved in the development of severe malarial anemia in children. However, IL‐3 and TGF‐β may offer protection against severe malarial anemia.